Asymmetric Cantilever Construction Control of a U-Shaped Box Concrete Continuous Bridge in Complex Environment - Haijun Zhou; Xuan Qi; Zhidong Liu; Wuqiang Xue; Jiuchun Sun; Jian Liu; Songbai Gui; Xia Yang (Buildings, 2023)
The bridge of Shanghai Metro Line 10 over Metro Line 6 is a U-shaped concrete single-box double-cell concrete box beam continuous bridge. A novel method is applied to construct the asymmetric cantilever prefabricated and assembled continuous bridge due to the limited construction space and the complex environment. Four mechanical state control methods are applied during the T-shape structure construction process: tensioning pre-stressed steel strand, jacking by the axial force servo system, adjusting the leg reaction force, and setting the auxiliary leg. Auxiliary measures such as the compressive column, side-span counterweight, and temporary pre-stressing are also taken into consideration. The finite element method simulations are performed to measure effects of the four control methods during the construction process. The front leg force of the bridge erection machine and the deflection of the bridge are then monitored. It was deduced that the simulated and measured values of the cantilever T-shape structure are controlled within the limit range during the construction process.